Identification and quantification of change in Australian illicit drug markets - Degenhardt Louisa; Koch Inge; Gilmour Stuart; Day Carolyn (BMC, 2006)
Abstract Background In early 2001 Australia experienced a sudden reduction in the availability of heroin which had widespread effects on illicit drug markets across the country. The consequences of this event, commonly referred to as the Australian 'heroin shortage', have been extensively studied and there has been considerable debate as to the causes of the shortage and its implications for drug policy. This paper aims to investigate the presence of these epidemic patterns, to quantify the scale over which they occur and to estimate the relative importance of the 'heroin shortage' and any epidemic patterns in the drug markets. Method Key indicator data series from the New South Wales illicit drug market were analysed using the statistical methods Principal Component Analysis and SiZer. Results The 'heroin shortage' represents the single most important source of variation in this illicit drug market. Furthermore the size of the effect of the heroin shortage is more than three times that evidenced by long-term 'epidemic' patterns. Conclusion The 'heroin shortage' was unlikely to have been a simple correction at the end of a long period of reduced heroin availability, and represents a separate non-random shock which strongly affected the markets.